The forgotten garden [compact disc, unabridged] - Morton, Kate, 1976- (Bolinda Audio Books ; Distributed by Brilliance Audio, 2008)
Cassandra is lost, alone and grieving. Her much loved grandmother, Nell, has just died and Cassandra, her life already shaken by a tragic accident ten years ago, feels like she has lost everything dear to her. But an unexpected and mysterious bequest from Nell turns Cassandra's life upside down and ends up challenging everything she thought she knew about herself and her family. Inheriting a book of dark and intriguing fairytales written by Eliza Makepeace - the Victorian authoress who disappeared mysteriously in the early twentieth century - Cassandra takes her courage in both hands to follow in the footsteps of Nell on a quest to find out the truth about their history, their family and their past; little knowing that in the process, she will also discover a new life for herself.